Algorithm of Calculating the Annual Economic Effect from Implementing Different Types of Innovation in a Business Organization - Parmacli, Dimitri (Olsztyn Economic Journal, 2012)
The goal of this article is the development of a commonly acceptable algorithm of calculating the economic effect from introducing innovations in a business organization. The article uses the method of absolute economic efficiency. It results in a number of suggested formulas for calculating the annual economic effect obtained by a reduction of manufacturing costs, increases in sales, savings of labour, material and financial resources both in manufacturing and non-manufacturing business areas, utilization of production waste as well as a reduction of manufacturing defects.